2018
DOI: 10.1002/jcu.22649
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bladder filling on uterine artery Doppler variables in the first trimester of pregnancy

Abstract: Objective: Uterine artery (UtA) Doppler examination is used in the first trimester to assess the risk of developing preeclampsia, with a standardized technique. However, the impact of bladder filling on UtA circulatory impedance in pregnancy has not been previously studied. This study aimed to examine the effect of bladder distension on UtA-pulsatility index (PI) and peak systolic velocity (PSV) in the first trimester of pregnancy. Methods:The authors conducted a prospective repeated-measure study on pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…There was no significant difference for age between the groups (mean 28.7 ± 5.0 vs 28.8 ± 5.01; p = 0.885). Gestational age was no significant difference between the groups [median 12 (11)(12)(13) vs 12 (11)(12)(13); p = 0.224]. Gravida and parity were similar between the groups (p > 0.05).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…There was no significant difference for age between the groups (mean 28.7 ± 5.0 vs 28.8 ± 5.01; p = 0.885). Gestational age was no significant difference between the groups [median 12 (11)(12)(13) vs 12 (11)(12)(13); p = 0.224]. Gravida and parity were similar between the groups (p > 0.05).…”
Section: Resultsmentioning
confidence: 94%
“…External factors affecting PI values of uterine artery Doppler have been investigated previously in the literature. The effects of parameters such as patient position and emptiness/fullness of bladder were explored [11,12]. The relationship between progesterone use and uterine artery Doppler at the 11 th -14 th gestational weeks has not been specifically investigated in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Serevalli et al [10] conducted a study on 45 pregnant women and they reported that they did not find any significant difference in the comparison of uterine artery Doppler measurements when bladder was full and empty. In their study conducted on 39 non-pregnant women, Battaglia et al [11] found significantly high Doppler indices when their bladders were full.…”
Section: Volume 27 | Issue 3 | December 2019mentioning
confidence: 99%
“…There are two studies in the literature performed on pregnant and nonpregnant women which investigate the impact of bladder fullness on the indices of uterine artery Doppler. [10,11] In our study, we aimed to investigate the impacts of the bladder fullness on the parameters of uterine artery Doppler in pregnant women.…”
Section: Original Articlementioning
confidence: 99%